Food acquisition and consumption by NOVA food classification and lived poverty index among rural and urban households in South Africa and Ghana - Nana Ama Frimpomaa Agyapong; Reginald Adjetey Annan; Florian Kroll; Charles Apprey; Linda Nana Esi Aduku; Robert Aidoo; Elizabeth Catherina Swart (Public Health Nutrition)
Abstract